If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 12 = 4t + -2 Reorder the terms: 12 + 5t = 4t + -2 Reorder the terms: 12 + 5t = -2 + 4t Solving 12 + 5t = -2 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 12 + 5t + -4t = -2 + 4t + -4t Combine like terms: 5t + -4t = 1t 12 + 1t = -2 + 4t + -4t Combine like terms: 4t + -4t = 0 12 + 1t = -2 + 0 12 + 1t = -2 Add '-12' to each side of the equation. 12 + -12 + 1t = -2 + -12 Combine like terms: 12 + -12 = 0 0 + 1t = -2 + -12 1t = -2 + -12 Combine like terms: -2 + -12 = -14 1t = -14 Divide each side by '1'. t = -14 Simplifying t = -14
| 26/27×18 | | -2x+19y=-17 | | 5x+5x+4x-4x+2x-3x=45 | | 15m+19m+6=0 | | -3x+7x=-20 | | 4a-9*2=3 | | 9b+5(2b+3)=41 | | 4(2n-3)=5n+9 | | 9/4/2 | | -6+r=49 | | .3x-4=.1(x-10) | | 8c+2(3+c)=46 | | -20u^4-17u^2-3=0 | | -42=q-15 | | 50-2X=100-7x | | f(x-1)=13 | | 9+2a+1=3a-8 | | 4x-22=62+2x | | -z+1=2-3y-x | | 3(x-2)-4(x+4)=-2(x-6) | | -14+3(x+10)=7(2x+5)-4 | | -7(6-7b)+6=-134 | | Z-2-3y=2x | | 6x-18=5x+15 | | h-49=13.8 | | 3x-1=7-3y+2 | | 16+144t+324t^2=0 | | 3(x-20)-4(x+4)=-2(x-6) | | 4c(a-6)+7(a-6)= | | X+2x=1050 | | -6(-1)-2y=12 | | 8c-7c=16 |